Delisting Medical Imaging in Private Settings from Public Coverage in Quebec - Amélie Quesnel-Vallée (McMaster University Library Press, 2013)
On December 19, 1981, the Québec government passed a bill allowing notably for the determination of public coverage of services based on location of delivery, opening the door to subsequent delisting of medical imaging (mammography, ultrasonography, computerized axial tomography scans and magnetic resonance imaging) when performed out of the hospital. Rationing and increased governmental regulatory powers were the explicit aims of this reform, with cost-efficiency an implicit aim. This reform occurred in the national context of decreased federal transfers for health, a severe recession, and on the provincial front, physicians in Québec had been without a contract since November 1979. The reform was achieved with regulatory instruments, with full implementation (delisting of public coverage of mammograms, ultrasonography, and thermography when outside of hospital) a year later. While the reform was never formally evaluated, it likely achieved its aim of cost-containment, but at the price of access in the public system, and at the risk of threats to horizontal and vertical equity.